The influence of life-event stress on two forms of the ischemic heartdisease: Myocardial infarct and stenocardia - Ausmanienė , Nomeda (Psichologija, 2000)
The work deals with the influence of life-event stress on two forms of the ischemic heart disease (IHD) -myocardial infarct and stenocardia. Three groups of 30 people in each were surveyed. The first group consisted of people after myocardial infarct, the second group - of people suffering from different extent of stenocardia without myocardial infarct, and the third one was formed of healthy people ( control group). The following methods were used for the research: Life Experiences Survey test (LES) for subjective evaluation of life events; Hospital Anxiety and Depression Scale for somatic patients (HAD); evaluation o f disease seriousness b y patients and doctors. The following aspects were evaluated when analyzing the results: influence of life-event stress on IHD; inter-group differences depending on anxiety and depression level, on number of life changes and their evaluation. Results of this study enabled to conclude that there are no statistically significant differences between healthy people and patients suffering from IHD in respect of the number of life changes, but the patients with IHD more often than healthy people use extremely negative evaluations when describing their experiences.